Clinical predictors of specialist treatment requirements in pelvic fracture: A retrospective cohort study. (July 2018) - Caulfield, Alexandra; Hamilton, William L; Trent, Louise; Ellington, Matt
Objectives and background: To describe the pelvic fracture population presenting to a district hospital in New Zealand and investigate whether clinical measurements can predict subsequent transfer to specialist tertiary care units. Early transfer to tertiary care is associated with improved surgical outcomes and cost-effectiveness, but there has as yet been little research into predictive markers for referral. Methods: Retrospective cohort study of all patients admitted with pelvic fracture to the intensive care unit of Hastings Memorial Hospital, New Zealand from 2005 to 2014. The primary outcome was transfer to specialist tertiary care. Secondary outcomes were total duration of hospitalisation and conservative vs. surgical management. Clinical variables including age, sex, observations and comorbidities were analysed against these outcomes using logistic regression. Results: Data from 40 patients were collected (24 male, 16 female; median age: 44 years). Median distance from the hospital was 22.6 km, with 27 (67.5%) patients transported by land and 13 (32.5%) arriving by helicopter. Median time from receipt of emergency call to arrival at hospital was 60 min. Three patients died and 14/40 (35%) required transfer to tertiary centres. Damage to intra-abdominal structures such as spleen, liver and bladder lacerations were associated with transfer to tertiary care, unadjusted relative risk 3.34 (95% confidence intervals: 1.39–8.05). Conclusion: Despite a 10-year recruitment window, only 40 patients were included in this study, limiting its statistical power. Nonetheless, our data suggest that pelvic fracture patients with injuries to intra-abdominal viscera are more likely to require tertiary care transfer.